Simultaneous Quantification of Brigatinib and Brigatinib-Analog in Rat Plasma and Brain Homogenate by LC-MS/MS: Application to Comparative Pharmacokinetic and Brain Distribution Studies - Bo Li; Min Lu; Lei Jin; Maoen Zheng; Peilu Sun; Shanshan Lei; Shan Xiong; Suhong Chen (International Journal of Analytical Chemistry)
Brigatinib and brigatinib-analog are potent and selective ALK inhibitors with the similar structure. A simple and sensitive high-performance liquid chromatography with tandem mass spectrometry (LC-MS/MS) method for simultaneous determination of brigatinib and brigatinib-analog in rat plasma and brain homogenate was developed and validated. Chromatographic separation was carried out on an ODS column with acetonitrile and 0.1% formic acid in water as the mobile phase with gradient elution at a flow rate of 0.5 mL/min. Detections were performed using a TSQ Quantum Ultra mass spectrometric detector with electrospray ionization (ESI) interface, which was operated in the positive ion mode. A simple protein precipitation preparation process was used. The lower limits of quantification (LLOQs) were 1.0 ng/mL and 0.5 ng/mL for analytes in rat plasma and brain homogenate, respectively. The intrabatch and interbatch precision and accuracy of brigatinib and brigatinib-analog were well within the acceptable limits of variation. The simple and sensitive LC-MS/MS method was successfully applied to the pharmacokinetic and brain distribution studies following a single oral administration of brigatinib and brigatinib-analog to rats. The above studies would lay a good foundation for the further applications of brigatinib and brigatinib-analog.